Usefulness of handheld ultrasound devices in the assessment of abdominal pathology and comparison with high-end ultrasound devices - Segura-Grau, Ana; Salcedo-Joven, Ines; Montes-Belloso, Esther; Cinza-Sanjurjo, Sergio; Segura-Fragoso, Antonio; Segura-Grau, Elena (The Ultrasound Journal, 2025)
Background and objective: The EFSUMB recommends the use of handheld ultrasound devices in many point-of-care cases, including primary care. However, it is necessary to continue training in conventional ultrasound examinations. Our aim is to analyze the diagnostic accuracy of handheld ultrasound devices in abdominal pathology compared with conventional high-end ultrasound scanners. Methodology: Agreement study between two ultrasound techniques, (1) POCUS (point-of-care ultrasound), with a General Electric® Vscan Air device and (2) standard ultrasound with a high-end Samsung RS 80® ultrasound scanner. Cohen’s kappa was used for the analysis. The study was conducted between November 2022 and September 2023 in the general ultrasound unit of the San Francisco de Asís University Hospital in Madrid. It included all patients from the emergency department and the inpatient unit who have been referred for abdominal ultrasound. Results: A total of 93 patients were included (52.7% were women and the mean age was 65.6 (23.6) years). As regards body mass index (BMI), 11.8% had a BMI over 30 kg/m2. Of the scans performed, 69.9% were abdominal and the rest urological. Overall, the degree of agreement between the two tests was 89%, with 100% for liver and bladder pathology, 86.2% for renal pathology and 82.5% for complicated renal pathology. Intestinal (73.3%) and pancreatic (58.1%) pathologies showed the lowest correlation. Conclusions: The degree of agreement of handheld devices is high (89%), especially in renal and bladder pathologies, where ultrasound is decisive in decision-making. The agreement is weaker in pancreatic and gastrointestinal tract pathologies.